2015
DOI: 10.1016/j.cbi.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene lactones of Moquiniastrum polymorphum subsp. floccosum have antineoplastic effects in Walker-256 tumor-bearing rats

Abstract: F1B, which is rich in sesquiterpene lactones, showed antitumor activity against Walker-256 carcinosarcoma. This effect may be, at least in part, related to the induction of apoptosis and inhibition of TNF-α signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
1
19
0
2
Order By: Relevance
“…Martins et al (2015) also demonstrated a reduced growth of the Walker 256 tumor. The present study is the first to describe the chemopreventive effects of this plant and its ability to prevent chemical carcinogenesis in the intestine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Martins et al (2015) also demonstrated a reduced growth of the Walker 256 tumor. The present study is the first to describe the chemopreventive effects of this plant and its ability to prevent chemical carcinogenesis in the intestine.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, our research group described the antineoplastic activity of this extract, its fractions, and isolated compounds in both in vitro and in vivo assays (Strapasson et al, 2012;Martins et al, 2015). The in vivo assays revealed that the dichloromethane fraction of this medicinal plant reduces the growth of Walker 256 carcinosarcoma (Martins et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sesquiterpene lactones, such as 11αH-13-dihydrozaluzanin C, 8-hydroxigochnatiolide A, 8-hydroxi-10-desoxigochnatiolide A, gochnatiolide A, gochnatiolide B, and 10-desoxygochnatiolide A, are considered the bioactive components of MPEE (Piornedo et al, 2011;Strapasson et al, 2012;Martins et al, 2015). Sesquiterpene lactones may interfere with some key biological processes, such as cell signaling, proliferation, and death/apoptosis, and mitochondrial respiration, all of which constitute the molecular basis of their diverse pharmacological activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Martins et al (2015) reported that Walker-256 tumor growth was inhibited when rats were treated with a dichloromethane fraction of M. polymorpha. In summary, MPEE is not mutagenic, has antimutagenic potential (preferably by bioantimutagenesis), and is able to reduce the mitotic index, resulting in cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation